2020
DOI: 10.1016/j.cortex.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term forms of neural adaptation: An ERP investigation of dynamic motion aftereffects

Abstract: Adaptation is essential to interact with a dynamic and changing environment, and can be observed on different timescales. Previous studies on a motion paradigm called dynamic motion aftereffect (dMAE) showed that neural adaptation can establish even in very short timescales. However, the neural mechanisms underlying such rapid form of neural plasticity is still debated. In the present study, short-and long-term forms of neural plasticity were investigated using dynamic motion aftereffect combined with EEG (Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…There is much more to be revealed about the neural mechanisms of compensation. The detailed mechanisms and substrates of adaptation are known to depend on the duration of adaptation 27 , 28 . Thus, it is worth questioning whether the neural compensatory mechanisms in astigmatism also depend on the duration of experience with astigmatism, from a few seconds, to hours, to years.…”
Section: Discussionmentioning
confidence: 99%
“…There is much more to be revealed about the neural mechanisms of compensation. The detailed mechanisms and substrates of adaptation are known to depend on the duration of adaptation 27 , 28 . Thus, it is worth questioning whether the neural compensatory mechanisms in astigmatism also depend on the duration of experience with astigmatism, from a few seconds, to hours, to years.…”
Section: Discussionmentioning
confidence: 99%
“…How can our findings be explained in the light of commonly observed reduction in visual activity over time, usually referred to as visual adaptation (Webster, 2015)? Visual adaptation has been observed on multiple time-scales in the visual system and can occur in time ranges matching the average duration of a fixation (∼400 ms) (Akyuz et al, 2020; Gutnisky & Dragoi, 2008). Although visual adaptation likely plays an important role in explaining the reduced decodability found in the present condition there still remain several open questions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kubová et al ( 1990 ) found that presenting horizontally drifting gratings, the 60% of 80 observers tested showed higher N2 amplitude in the right hemisphere with respect to the left one. In addition, Akyuz et al ( 2020 ) using EEG and source localization showed that adaptation to directional motion was dominant in the left hemisphere; (ii) instead of analysing data from single electrodes, we pooled data across groups of electrodes (i.e. for Left, Central and Right regions) to measure the average modulation of cortical activity around the stimulation electrode.…”
Section: Methodsmentioning
confidence: 99%